Les pratiques des organismes en prévention des TMS : Terrain de recherche et chercheur de terrain - René Brunet (Perspectives Interdisciplinaires sur le Travail et la Santé)
This study investigated the contribution of prevention organizations’ practices to research into the prevention of musculoskeletal disorders (MSDs). In general, the gathering of critical information regarding prevention interventions is the result of both applied and action research. However, is this produced and necessary information sufficient to meet the requirements of the participants’ practices, in particular those of prevention organizations ? The author proposes some benchmarks to alert the scientific community to the methodological impasses and limitations of the areas of research. In particular, he questions :1. the work requested in relation to the institutional demands2. the methods used to follow the intervention over its duration3. the absence of small businesses and networks in the choice of areas of research.In view of the difficulties in controlling the evolution of the MSD phenomenon, the experience of prevention organizations may be a valuable information resource for research. Agreeing on conditions so that practitioners participate in this research effort is therefore a major challenge.